PROCEEDINGS OF the 29th Quadrennial Session of the CIE 2019
DOI: 10.25039/x46.2019.op49
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Colorimetric Analysis of the Cie Standard General Skies

Abstract: This paper studies the colorimetric characteristics of daylight within the framework of the CIE Standard General Skies. The correlated colour temperatures (CCTs) were studied based on long-term measurements. The colorimetric analysis employed in this study comprises: (i) the CCT occurrence; (ii) the CCT ranges; (iii) the CCT variation depending on the solar altitude; in function of season, time of day, and orientation, all corresponding to the fifteen CIE Standard Skies. The last part of the analysis illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Whereas the CCT occurrence might vary for different seasons and different sky conditions (Collins 1965, Rusnák 2014, Diakite and Knoop 2019, the first analysis of measurements indicates that there is no seasonal nor a weather dependancy in the trend of the local daylight locus (Figure 11, Figure 12). The latter simplifies the documentation of measurements for the daylight locus and reconstruction evaluation, as prevailing sky type, typically derived from luminance measurements or cloud cover maps, is not an essential parameter to document.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the CCT occurrence might vary for different seasons and different sky conditions (Collins 1965, Rusnák 2014, Diakite and Knoop 2019, the first analysis of measurements indicates that there is no seasonal nor a weather dependancy in the trend of the local daylight locus (Figure 11, Figure 12). The latter simplifies the documentation of measurements for the daylight locus and reconstruction evaluation, as prevailing sky type, typically derived from luminance measurements or cloud cover maps, is not an essential parameter to document.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were conducted at the daylight measuring site of the Technische Universität Berlin (52°31' N, 13°20' E, altitude 50 m), in an urban setting with medium height buildings and a mixture of low luminous turbidity and polluted atmosphere (Aydinli et al 2018, confirmed by the occurrence of CIE General Sky Type 12 and Sky Type 13 under clear sky conditions, reported in Diakite and Knoop 2019). Spectral radiance measurements of skylight without direct sunlight were performed by a custom-made spectral sky scanner with an array spectroradiometer (Zeiss Multi-Channel-Spectrometer MCS CCD with a Hamamatsu back-thinned CCD) using a step size of approximately 0,8 nm between 280 nm and 980 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future studies, vertical CCT records on the façade are planned as the spectral characteristics and the resulting CCTs depend on the orientation of the part of the sky being analysed, 65,66 and therefore, vertical records would better represent the spectral power distribution of daylight striking the window.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of visual, spectral, and colour difference comparisons between LARK and ALFA for different urban environments can be found in the paper by Balakrishnan and Jakubiec (2019). If spectral characteristics of daylight on the façade are relevant, spectral sky models based on patch measurements or integral measurements on titled planes are preferred, as the spectral power distribution of specific regions of the sky can vary largely (Nayatani andWyszecki 1963, Diakite andKnoop 2019b). Horizontally positioned integral measurements, which cover a smaller CCT bandwidth, will provide information about an average condition for assessments in which the assessment direction is unknown or variable.…”
Section: Alfamentioning
confidence: 99%